Digital Transformation of National Postal Operators - Srimbetova Dinara Anvarovna (Zien Journals, 2022)
The digital transformation of national postal operators can serve the development of digital economies, ecommerce, businesses and citizens. This can be facilitated by the introduction of new digital services, the creation of a favorable ecosystem for e-commerce, the reduction of delivery times due to new sorting lines, the launch of drones, the use of virtual cashiers and consultants, the robotization of digital offices and other smart initiatives
Keywords: Digital transformation; digital economy; digital Uzbekistan; digital technologies